" Does Educational level Affect the Outcome of Myocardial Infarction? " - Elsayed, Ahmed Magdy Ahmed (AUC Knowledge Fountain, 2024)
Background: Heath awareness plays a major role in determining the outcomes of serious medical conditions specially when response time is crucial. STEMI patients are prone to serious compilations if they didn’t receive the appropriate treatment on time. Raising the health awareness of the community would result in seeking medical help at earlier stage of the disease. Earlier presentation to the medical center would result in better health outcomes. Certain factors form the health awareness of the community. This includes educational level, previous exposure to similar situations, and exposure to health awareness materials. Methods: This is a cohort study in the National Heart Institute in Egypt following up STEMI patients undergoing primary PCI during their hospital stay. Correlation between educational level, health awareness, and time of arrival to ER and in hospital complications during hospital stay was assessed. Results: Data of 166 patients were analyzed showing significant correlation between health awareness and time of presentation to the ER in STEMI patients (P: Conclusion: Education level and Health awareness of cardiac symptoms are associated with early presentation to the ER in STEMI patients. However, this didn’t result in a significant change in the outcomes of STEMI due to a delay in the time to catheterization compared to the international standards.